Maternal substance use during pregnancy and associated factors in Adama, central Ethiopia - Mohammed, Kimiya; Shawel Getahun, Mihiret; Abera Belachwe, Yohanes; Mohammed Fati, Nesra; Mekuria Negussie, Yohannes (Frontiers in Global Women's Health, 2025)
BackgroundSubstance use, including tobacco, alcohol, khat, and illicit drugs, is a significant preventable contributor to the global burden of disease. Women are particularly vulnerable during their reproductive years, with substance use during pregnancy posing serious risks to maternal and fetal health. Therefore, this study aimed to assess of prevalence of substance use and determine associated risk factors among pregnant women in Adama, Central Ethiopia.MethodsA health facility-based cross-sectional study was conducted among 472 pregnant women. Participants were selected using a systematic sampling technique. Data were collected through an interviewer-administered structured questionnaire. Binary logistic regression was employed to model the association between substance use and explanatory variables. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were used to estimate the strength of association. Statistical significance was determined at a p-value < 0.05.ResultThe overall prevalence of substance use during pregnancy was 22.0% (95% CI: 18.2–26.0). Unplanned pregnancy (AOR = 3.49, 95% CI: 1.23–9.89), pre-pregnancy substance use (AOR = 24.16, 95% CI: 11.49–40.82), husband/partner substance use (AOR = 4.51, 95% CI: 1.44–14.20), and ever heard about the side effects of substance use (AOR = 14.60, 95% CI: 5.31–17.65) were factors significantly associated with maternal substance use during pregnancy.ConclusionNearly one in four pregnant women reported using substances during pregnancy. Educational and counseling interventions during antenatal care should emphasize the risks of substance use on maternal health and fetal development, particularly targeting women with a history of substance use or unplanned pregnancies. Efforts should also involve partners and employ community-based strategies to raise awareness of these risks.